DAMPAK UTILITARIAN VALUE DAN EXPERIENTIAL MARKETING TERHADAP CUSTOMER SATISFACTION DAN REVISIT INTENTION - Wulanjani, Harimurti; Derriawan, Derriawan (Economic Faculty, Attahiriyah Islamic University, 2017)
This research was conducted in the Restaurant area of Taman Kencana Bogor Restaurant with a view to determining whether the attribute Experiential Marketing and Food Quality on Customer Satisfaction, which in the end as a determinant Revisit Intention Customers in Region Restaurants Taman Kencana Bogor. The method used is a descriptive quantitative method, samples of this study were 200 respondents as the basic criteria for SEM, all the respondent collected by purposive sampling. These results indicate that the variable Experential Marketing and Food Quality has a positive and significant impact on Customer Satisfaction, as well as variable Experiential Marketing, Food Quality and Customer Satisfaction after testing has a positive and significant effect on the variable Revisit Intention. Keywords: revisit intention, experiential marketing, food quality, customer satisfaction